2021
DOI: 10.1590/1516-4446-2019-0726
|View full text |Cite
|
Sign up to set email alerts
|

BDNF Val66Met polymorphism and resilience in major depressive disorder: the impact of cognitive psychotherapy

Abstract: Objective: Clinical and biological correlates of resilience in major depressive disorder are scarce. We aimed to investigate the effect of the Val 66 Met polymorphism in the BDNF gene on resilience scores in major depressive disorder patients and evaluate the polymorphism's moderation effect on resilience scores in response to cognitive therapy. Method: A total of 106 major depressive disorder patients were enrolled in this clinical randomized study. The Resilience Scale and the Hamilton Rating Scale for Depre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…The second most frequently investigated gene was Brain-Derived Neurotrophic Factor ( BDNF) ( n = 5). All five of the studies reviewed investigated SNP rs6265 in exon 11 of the BDNF gene ( 105 , 116 , 122 , 129 , 131 ). Of the four studies, three found Val/Val homozygous genotype to be associated with resilience, while two studies found the Met allele to be associated with resilience.…”
Section: Resultsmentioning
confidence: 99%
“…The second most frequently investigated gene was Brain-Derived Neurotrophic Factor ( BDNF) ( n = 5). All five of the studies reviewed investigated SNP rs6265 in exon 11 of the BDNF gene ( 105 , 116 , 122 , 129 , 131 ). Of the four studies, three found Val/Val homozygous genotype to be associated with resilience, while two studies found the Met allele to be associated with resilience.…”
Section: Resultsmentioning
confidence: 99%
“…When observing only the BDNF Val66Met (rs6265) genetic variant frequency and genotypic distribution (Table 1), the GG (Val/Val) genotype was frequent in more than 50% of the MDD sample studied in 65% of the analyzed studies [17,18,19,21,23,25,26,[30][31][32][33] (Figure 3). Its frequency is lower in only few studies [16,20,22,[27][28][29].…”
Section: Bdnf Gg (Val/val) Genotype Frequency In Differentmentioning
confidence: 99%
“…In addition to pharmacological treatments and transcranial stimulation focused on MDD, cognitive therapies are indicated to patients with MDD to help with resilience-known as an individual's ability to deal with stress or trauma, for example [18]. Regarding BDNF Val66Met (rs6265) polymorphism, Peters et al [18] noted that participants with an A (Met) allele presented higher resilience scores compared to those of the GG (Val/Val) genotype (p = 0:037). Furthermore, cognitive therapy improved resilience (p = 0:001) and reduced depressive effects (p = 0:001), depending on their sex (p = 0:008) and genetic susceptibility (p = 0:048) [18].…”
Section: Bdnf Genetic Variant and Treatment Responsementioning
confidence: 99%
See 1 more Smart Citation
“…A prior study demonstrated a positive correlation between BDNF levels and the function of the central nervous system and peripheral nervous system [8]. Moreover, BDNF, expressed in the brain, is involved in the development of mental disorders, and studies show that peripheral BDNF can potentially be used as a marker of these diseases in humans [9]. Previously, we demonstrated that autoimmune thyroiditis (AIT) and hypothyroidism could affect the transcription of the genes involved in neurogenesis, nerve impulse transmission, and cell cycle regulation [10], [11], 12], [13], [14].…”
Section: Introductionmentioning
confidence: 98%